Neonatal screening for severe combined immunodeficiency in Brazil - Marilia Pyles Patto Kanegae; Lucila Akune Barreiros; Juliana Themudo Lessa Mazzucchelli; Sonia Marchezi Hadachi; Laura Maria de Figueiredo Ferreira Guilhoto; Ana Lúcia Acquesta; Isabel Rugue Genov; Silvia Maia Holanda; Regina Sumiko Watanabe Di Gesu; Ana Lucia Goulart; Amélia Miyashiro Nunes dos Santos; Newton Bellesi; et al. (Jornal de Pediatria, 2016)
Objective: To apply, in Brazil, the T-cell receptor excision circles (TRECs) quantification technique using real-time polymerase chain reaction in newborn screening for severe combined immunodeficiency and assess the feasibility of implementing it on a large scale in Brazil. Methods: 8715 newborn blood samples were collected on filter paper and, after DNA elution, TRECs were quantified by real-time polymerase chain reaction. The cutoff value to determine whether a sample was abnormal was determined by ROC curve analysis, using SSPS. Results: The concentration of TRECs in 8,682 samples ranged from 2 to 2,181 TRECs/μL of blood, with mean and median of 324 and 259 TRECs/μL, respectively. Forty-nine (0.56%) samples were below the cutoff (30 TRECs/μL) and were reanalyzed. Four (0.05%) samples had abnormal results (between 16 and 29 TRECs/μL). Samples from patients previously identified as having severe combined immunodeficiency or DiGeorge syndrome were used to validate the assay and all of them showed TRECs below the cutoff. Preterm infants had lower levels of TRECs than full-term neonates. The ROC curve showed a cutoff of 26 TRECs/μL, with 100% sensitivity for detecting severe combined immunodeficiency. Using this value, retest and referral rates were 0.43% (37 samples) and 0.03% (3 samples), respectively. Conclusion: The technique is reliable and can be applied on a large scale after the training of technical teams throughout Brazil. Resumo: Objetivo: aplicar no Brasil a técnica de quantificação de T-cell Receptor Excision Circles (TRECs) por polymerase chain reaction em tempo real para triagem neonatal de imunodeficiência combinada grave (SCID) e avaliar se é possível realizá-la em larga escala em nosso país. Métodos: foram coletadas 8.715 amostras de sangue de recém-nascidos em papel filtro e, após eluição do DNA, os TRECs foram quantificados por polymerase chain reaction em tempo real. O valor de corte para determinar se uma amostra é anormal foi determinado pela análise de curva ROC utilizando-se o programa SSPS. Resultados: a concentração de TRECs em 8.682 amostras analisadas variou entre 2 e 2.181 TRECs/μL de sangue, com média e mediana de 324 e 259 TRECs/μL, respectivamente. 49 (0,56%) amostras ficaram abaixo do valor de corte (30 TRECs/μL) e foram requantificadas. Quatro (0,05%) mantiveram resultados anormais (entre 16 e 29 TRECs/μL). Amostras de pacientes com diagnóstico clínico prévio de imunodeficiência combinada grave e síndrome de DiGeorge foram utilizadas para validar o ensaio e todas apresentaram concentração de TRECs abaixo do valor de corte. Recém-nascidos prematuros apresentaram menores níveis de TRECs comparados aos nascidos a termo. Utilizando a curva ROC em nossos dados, chegamos ao valor de corte de 26 TRECs/μL, com sensibilidade de 100% para detecção de imunodeficiência combinada grave. Utilizando este valor, as taxas de repetição e encaminhamento, ficaram em 0,43% (37 amostras) e 0,03% (3 amostras), respectivamente. Conclusão: A técnica é factível e pode ser implantada em larga escala, após treinamento técnico das equipes envolvidas. Keywords: SCID, Neonatal screening, TRECs, T lymphocytes, Combined immunodeficiency, Primary immunodeficiency, Palavras-chave: SCID, Triagem neonatal, TRECs, Linfócitos T, Imunodeficiência combinada, Imunodeficiência primária